Tổng hợp, nghiên cứu phức chất của europi với L-methionin - Uyển, Nguyễn Trọng; Thiềng, Lê Hữu; Thủy, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The complex of europium with L. methionine have been isolated on solid state. The complex has the formula H3[Eu(Met)3(NO3)3]. The structure of the complex was determined by thermal composition and IR spectral methods